Bottle neck around penile neck-3 rare case reports - Udapudi, Deepak G.; Kalke, Siddharth Vijay; Nayak, Madhavi (International Surgery Journal, 2018)
A variety of metallic and non-metallic rings causing constriction to the external genitalia have been described in the literature across all ages. The adult population frequently reports erotic or autoerotic goals when intentionally placing constricting devices. In adults these constricting bands are placed deliberately by the person himself to influence blood circulation and thereby obtain prolonged erection and/or sexual pleasure. A compilation of 3 rare case presentations in the casualty of JJM Medical College Davangere were collected and studied. The present case series shows that sexual perversions can present as rare surgical emergencies and need aggressive early intervention to avoid vascular compromise and its squeal.